Diagnostic accuracy of CAPD and SOS-PD in detecting delirium infants: A systematic review - Alfin Nugroho; Mega Hasanul Huda; Siti Chodidjah; Lhesmi Tri Yana Putri Simanjuntak (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Delirium in infants admitted to the neonatal intensive care unit (NICU) is a critical but often underrecognized condition. The Cornell assessment of pediatric delirium (CAPD) and Sophia observation withdrawal symptoms–pediatric delirium (SOS-PD) are used for early detection, yet their diagnostic accuracy in infants remains unclear. Purpose: To evaluate the sensitivity, specificity, and validity of CAPD and SOS-PD in detecting delirium among infants. Method: A systematic review was conducted on observational diagnostic validation studies published in the last ten years involving infants. Searches were performed in PubMed, ProQuest, ScienceDirect, SAGE Journal, Taylor & Francis, Cochrane, and Clinical Key. Risk of bias was assessed using QUADAS-2, and data were synthesized narratively. Results: Seven studies met the inclusion criteria. CAPD showed sensitivity of up to 94.1% and specificity of 79.2%, while SOS-PD demonstrated sensitivity of 92.3% and specificity of 96.5%. A major challenge was distinguishing delirium from iatrogenic withdrawal syndrome (IWS). Conclusion: CAPD and SOS-PD are valid and reliable tools for delirium screening in NICU infants, supporting early detection and improving patient safety and quality of care.